Automatic Feeding Machine for Freshwater Prawn Precision Farming - KHAIRUDDIN, MUHAMAD KHAIRUL IRFAN; A MAJID, HUDA (Progress in Engineering Application and Technology, 2023)
An automated feeding machine is a device that feeds the giant freshwater prawn at a set time. This research is to determine the effective frequent feeding and feed amount per feeding on giant freshwater prawn survival and growth. The machine will have a DC motor, a giant freshwater prawn tank, a feeding tank, an Arduino UNO, a Buck converter, a relay, a gear, and a belting. The feed from the tank will be dropped via a hole in the mechanism to feed the giant freshwater prawn. The analysis intended to reduce feeding rate variances and guarantee that subsequent statistical analyses have enough power to detect changes in feeding rates consistently. For future studies, the features for monitoring system parameters can be added in such cases to monitor the amount of feed (grams).